Factors that Influence the Growth of the Indonesian Economy - Prabawati, Achadyah; Hotima, Siti Husnul; Suryadinata, Ningrum; Rohim, Rohim; Aulia, Rizqyna Ega (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2025)
Economic growth can be assessed in Gross Domestic Product, because it shows the production capacity, income and expenditure of the country. In accordance with the dynamics of population growth in the modern world with economic and social developments which are also followed by an increase in people's consumption patterns. This increases the productivity of consumer goods which will increase tax revenues. The problems that occur are 1) Is there a significant influence simultaneously and partially between population growth, the amount of public consumption and tax revenues by the state on Indonesia's economic growth? 2) How is the intervening relationship between population growth, the amount of public consumption and tax revenues by the state on Indonesia's economic growth. Research with quantitative methods using Linear Regression analysis and Path Analysis will analyze secondary data from 1991-2023 produced by Bank Indonesia and the Indonesian Central Statistics Agency. The results of the study are: 1) Population growth, consumption and tax revenues have a significant simultaneous effect on the Indonesian economy. 2) Consumption and tax revenues have a significant partial effect on the Indonesian economy. 3) Population growth and consumption have a significant partial effect on tax revenues. 4) Population growth has a significant partial effect on consumption. 5) Population growth is related to the Indonesian economy with consumption intervening. 6) Population growth is related to the Indonesian economy with tax revenue intervening. 7) Consumption is related to the Indonesian economy with tax revenue intervening